2017
DOI: 10.3390/nano7100340
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Photovoltaic Performance Using Broadband Luminescent Down-Shifting by Combining Multiple Species of Eu-Doped Silicate Phosphors

Abstract: This paper demonstrates the application of a broadband luminescent downshifting (LDS) layer with multiple species of europium (Eu)-doped silicate phosphors using spin-on film technique to enhance the photovoltaic efficiency of crystalline silicon solar cells. The surface morphology of the deposited layer was examined using a scanning electron microscope (SEM). The chemical composition of the Eu-doped silicate phosphors was analyzed using energy-dispersive X-ray spectroscopy (EDS). The fluorescence emission of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Several studies showing improvements in solar cells performance with distinct LDS phosphors were reported, such as organic dyes 9,10 , quantum dots (QDs) 9 , and lanthanide ions (Ln 3+ ) coordination complexes 6,7,[9][10][11][12][13][14][15][16][17][18] . The reasons for the wide utilization of Ln 3+ complexes (europium, Eu 3+ , and terbium, Tb 3+ ) are related to their strong emission and photostability and also the emission profile in the visible spectral range, which overlaps the absorption of c-Si solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showing improvements in solar cells performance with distinct LDS phosphors were reported, such as organic dyes 9,10 , quantum dots (QDs) 9 , and lanthanide ions (Ln 3+ ) coordination complexes 6,7,[9][10][11][12][13][14][15][16][17][18] . The reasons for the wide utilization of Ln 3+ complexes (europium, Eu 3+ , and terbium, Tb 3+ ) are related to their strong emission and photostability and also the emission profile in the visible spectral range, which overlaps the absorption of c-Si solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a down‐conversion (DC) process, a high‐energy incident photon is absorbed by the DC phosphors and re‐emitted as two or more lower energy photons at wavelengths where the silicon solar cells exhibit a strong spectral response . A number of researchers have shown that there is significant enhancement in conversion efficiency of solar PV devices by integrating a down‐converting or luminescent down‐shifting (LDS) layer on the top surface of c‐Si solar cells …”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has gone into the creation of high-efficiency single-junction solar cells by overcoming the conversion efficiency limit. This has led to the development of multiple bandgap tandem cells [7,8,9,10,11], intermediate bandgap cells [12,13,14], down-conversion (DC) cells [15,16,17,18,19,20], up-conversion (UC) cells [21,22,23,24,25,26], and luminescent downshifting (LDS) cells [27,28,29,30]. In recent years, luminescent-phosphors materials for DC, UC, and LDS, which are capable of converting a broad spectrum of light into photons of particular wavelengths, have been synthesized and used to minimize the losses in the photovoltaic device energy conversion process.…”
Section: Introductionmentioning
confidence: 99%